(untitled) (Environment & Health, 2017)
Objective. We determined the influence of the landfills of solid domestic waste (SDW) (by the way of the example of the SDW landfill of Kyiv-Sviatoshynsky industrial management of housing and communal services in the village of Kriukіvshchina) on the environment and the health of the population in the adjacent settlements. Materials and methods. Results of the sample analyses of ambient air, soil, water of centralized drinking water supply, groundwater wells, and surface water were the materials of the study. The study was performed by the standard procedures. Data analysis of the morbidity of the population according to the statistical reporting was carried out in 4 settlements in 2012- 2015. For the independent assessment of the health status of the residents in the areas adjacent to the SWD landfill we developed a questionnaire and performed a survey of the population (89 questionnaires). Results. In Ukraine, 95% of the SDW are landfilled and only a small percentage on the engineering structures – polygons. By the way of the example of the SWD landfill of Kyiv-Sviatoshinsky regional management of housing and communal services in the village of Kriukіvshchina we showed that landfills were not technically equipped. They are located and operate with the violations of the requirements of sanitary legislation. The landfills are the main factors of the contamination of underground and surface water, soils, ambient air in the region of their location. A zone of the influence on ambient air goes beyond the normative sanitary protection zone (500 m). Significant point soil pollution with heavy metal compounds was detected at a distance over 100 m from the landfill. A filtrate is a main negative factor of the landfill influence on the environment. The foreground pollutants of the landfill filtrate are: difficult for biological degradation organic substances (by the indices of COD, BOD5), ammonia, salt-containing substances, chlorides, heavy metals. A zone of the influence on surface water and groundwater for domestic-drinking needs reaches several kilometers. The negative influence of the landfills on the environment significantly affects the living conditions of the population, including health indices. The incidence rate of cardiovascular and respiratory diseases of the population in the villages adjacent to the SDW landfill exceeds significantly the analogous average regional indices. A clear tendency to an increase of the morbidity indices is observed at the reduction of the distance from the settlement to the landfill.